Determinants of using pacifier and bottle feeding - Buccini, Gabriela dos Santos; Benício, Maria Helena D'Aquino; Venancio, Sonia Isoyama (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the factors associated with the use of pacifiers and/or bottle feeding in infants aged under one year. METHODS This is a cross-sectional study with 34,366 children and using data from the database of the 2nd Nationwide Survey of Breastfeeding Prevalence performed in the Brazilian capitals and Federal District in 2008. Cluster sampling was used. The questionnaire included questions about the use of artificial nipples in the last 24 hours. The analysis considered three outcomes: exclusive use of pacifier, exclusive use of bottle feeding, and use of artificial nipples (pacifier and bottle feeding). Prevalence ratios were obtained using Poisson regression with robust variance following a hierarchical model. RESULTS The following factors were associated with exclusive use of the pacifier: mother working outside the home, primiparity, child was not breastfed within the first hour, and child had consumed tea on the first day at home. The following factors were associated with exclusive use of bottle feeding: mother working outside the home, primiparity, low birth weight, child not breastfed within the first hour, and child had consumed milk formula and tea on the first day at home. The following factors were associated with use of artificial nipples (pacifier and bottle feeding): mother working outside the home, primiparity, cesarean delivery, the male gender, low birth weight, born in a hospital not accredited as “baby friendly”, required health baby monitoring in the Primary Health Care Unit (PR = 0.91), and child had consumed milk formula, water, or tea on the first day at home. CONCLUSIONS This study identified profiles of exclusive users of pacifiers, bottle feeding, and both. The provided information can guide preventive practices for child health.